Decolonizing the Way Libraries Organize - White, Hollie (2018)
Knowledge organization systems (KOSs) are social constructs that represent the needs and knowledge of specific communities at specific times and places (Olsen, 1998; Svenonius, 2000; Hunter, 2009). Libraries use knowledge organization systems like cataloging codes, classification schemes, and languages of aboutness to describe the information objects they hold. These structures are central to library cataloging (Farnel, 2017). Because library KOSs reflect the biases of the time periods and places they were created, applications of these systems outside of those contexts are potentially problematic in terms of gender, culture, and ethnic exclusion (Olsen, 1998; Alemu & Stevens, 2015). Many of the systems used in libraries throughout the world originated in the United States or Europe. It is time to consider the impact that these systems have outside of their designated contexts and how to integrate other perspectives. The purpose of this paper is to question the cultural suitability of the systems and procedures libraries have in place to organize materials. As stated by Berman, the systems and approaches that catalogers adhere to are “so slavish” (Berman & Gross, 2017). When librarians talk about changes to codes and standards that are currently in use, it is often at the micro-level. These micro-level changes include submitting a term addition or term change request to the Library of Congress Subject Headings; or adding/revising a rule to Resource Description and Access. What may be needed are not these micro-level changes, but changes at the macrolevel. Librarians need to feel empowered to go beyond the Euro-American models of library cataloging work, without feeling that they are violating the integrity of their relationships with networks and consortia. Structures need to be in place to allow libraries and catalogers to vary the way they apply the necessary guidelines. Specific examples—with an emphasis on Southeast Asia -- is presented to argue these points.